Chrysin modulates protein kinase IKKε/TBK1, insulin sensitivity and hepatic fatty infiltration in diet‐induced obese mice. Issue 1 (5th August 2021) - Amir Siddiqui, Mohammad; Badruddeen,; Akhtar, Juber; Uddin, Shahab; Chandrashekharan, Sidda Madappa; Ahmad, Mohammad; Khan, Mohammad Irfan; Khalid, Mohammad
Abstract: Nuclear factor kappa B cells (NF‐κB) activation causes induction of the noncanonical IκB kinases (I‐kappa‐B kinase epsilon (IKKε) and TANK‐binding kinase 1 (TBK1) in liver and fat after high fat diet which followed activating of cascade of counter‐inflammation that conserves energy storage. Chrysin (5, 7‐dihydroxyflavone), a natural flavonoid, present in many plants, honey and propolis, used conventionally to treat numerous ailments. The present study was aimed to identify the protective role of chrysin on the glucose lowering and insulin sensitivity in diet induced obese (DIO) mice by regulating IKKε/TBK1. Chrysin administered therapeutically (60, 100, 200 mg/kg body weight) and preventive mode (200 mg/kg body weight) for 4 and 10 weeks respectively to DIO mice. At last fasting blood glucose, oral glucose tolerance test, serum lipid profile, as well as the expression level of IKKε/TBK1 and triglyceride in the liver tissue were assessed. DIO mice showed impaired glucose tolerance, reduced weight gain, elevated hepatic IKKε/TBK1 expression, fatty acid infiltration triglyceride and increased in plasma insulin and glucose. Chrysin in both therapeutic and preventive mode normalized the altered levels of the same. Overall chrysin improves glycemic control and insulin sensitivity through regulating expression of IKKε/TBK1 in liver of DIO mice.